High-temperature terahertz quantum-cascade lasers: design optimization and experimental results - D. V. Ushakov; A. A. Afonenko; I. A. Glinskiy; R. A. Khabibullin (Российский технологический журнал)
Objectives. Terahertz quantum-cascade lasers (THz QCLs) are compact solid-state lasers pumped by electrical injection to generate radiation in the range from 1.2 to 5.4 THz. The THz QCL operating frequency band contains absorption lines for a number of substances that are suitable for biomedical and environmental applications. In order to reduce the size and cost of THz QCLs and simplify the use of THz sources in these applications, it is necessary to increase the operating temperature of lasers.Methods. To calculate electron transport in THz QCLs, we used a system of balance equations based on wave functions with reduced dipole moments of tunnel-bound states.Results. As a result of the calculations, an original band design with a period based on three GaAs/Al0.18Ga0.82As quantum wells (QWs) and a gain maximum at about 3.3 THz was proposed. Based on the developed design, a THz QCL was fabricated, including the growth of a laser structure by molecular beam epitaxy, postgrowth processing to form strip lasers with a double metal waveguide, as well as an assembly of lasers mounted on a heat sink. The developed THz QCLs was capable of lasing at temperatures of up to 125 K as predicted by the performed calculations. We also studied band designs based on two GaAs/AlxGa1–xAs QWs having varying aluminum contents in the barrier layers (x = 0.20, 0.25, and 0.30).Conclusions. The calculated temperature dependences of the peak gain for two-QW designs with x > 0.2 confirm the possibility of creating THz QCLs operating at temperatures above 200 K. Thus, we have proposed two-QW band designs that outperform existing high-temperature designs in terms of maximum operating temperature.